Exploring the Ruthenium-Ligands Bond and Their Relative Properties at Different Computational Methods - Adebayo A. Adeniyi; Peter A. Ajibade (Journal of Chemistry)
We report some experimental bond distances and computational models of six ruthenium bonds obtained from DFT to higher computational methods like MP2 and CCSD. The bonds distances, geometrical RMSD, and the thermodynamic properties of the models from different computational methods are similar. It is observed that optimization of molecules of many light atoms with different functional methods results in significant geometrical variation in the values and order of the computed properties. The values of the hyperpolarizabilities, HOMO, LUMO, and isotropic and anisotropic shielding are found to depend greatly on the type of the functional used and the geometrical variation rather than on the nature of basis set used. However, all the methods rated modelled Ru-S, Ru-Cl, and Ru-O bonds as having the highest hyperpolarizabilities values. The infrared spectra data obtained from the different computational methods are significantly different from each other except for MP2 and CCSD which are found to be very similar.